FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU PENGELOLAAN KEUANGAN MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Helpita; Gusnardi; Hendripides (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This study aims to determine the effect of financial knowledge, financial attitudes and locus of control on financial management behavior of students of the Economic Education Study Program, FKIP University of Riau. The population in this study were active undergraduate students of the Economic Education Study Program, FKIP University of Riau, batch 2018 and 2019 both male and female who lived in boarding houses with a total of 88 students. The sample of this study amounted to 88 students with the sampling technique using the saturated sampling technique. The data collection method uses a questionnaire distributed through google forms and the collected data is then tabulated and analyzed using multiple linear regression. Hypothesis testing was carried out with partial and simultaneous significant tests. Based on the results of the study, it was found that the coefficient of determination (R2) was 0.440, which means that 44% of financial management behavior was influenced by financial knowledge, financial attitudes and locus of control while the remaining 56% was influenced by other independent variables not included in this study. Future research is expected to be able to examine other variables other than the three variables in the study. Keywords: Financial Knowledge, Financial Attitude, Locus Of Control, Financial Management Behavior